ChemInform Abstract: Biphilic Organophosphorus Catalysis: Regioselective Reductive Transposition of Allylic Bromides via PIII/PV Redox Cycling. Issue 38 (3rd September 2015) - Reichl, Kyle D.; Dunn, Nicole L.; Fastuca, Nicholas J.; Radosevich, Alexander T.
Abstract The reductive transposition of primary allylic halides is catalyzed by a biphilic organophosphorus catalyst.